The pest complex Cryptoblabes gnidiella (Milliere) (Lepidoptera: Pyralidae) and Planococcus citri (Riáo) (Homoptera: Pseudococcidae) on sweet orange groves (Citrus sinensis (L.) Osbeck) in Portugal: interspecific aáociation - Silva, E. B.=700 1 Mexia, A.
Resumenes (Es, En)